Karakteristik Mutu Sabun Cair Alami Komposit Dengan Penambahan Kolagen Kulit Ikan Tuna (Thunnus albacores) - Sudin, Sumarni (Transbahasa, 2024)
This study aims to analyze the quality of natural liquid soap extracts of cucumber (Cucumis sativus L.) and lime (Citrus aurantifolia S.) with the addition of tuna skin collagen (Thunnus albacores), describe the level of preference (hedonic) of panelists towards natural liquid soap and determine the selected product. This study consisted of two stages: the preliminary, which aims to obtain collagen. The main résearch aims to determine the formula of natural liquid soap with collagen concentration treatment of 1%, 3%, and 5% and characterize the quality of natural liquid soap. The parameters tested included collagen yield and chemical characteristics, which were analyzed descriptively, the hedonic value of soap, which was analyzed using Kruskal Wallis, and viscosity of liquid soap designed with RAL and analyzed with ANOVA and Duncan. The selected product was determined using Bayes' test, which was then tested for pH, foam stability, free fatty acids, and Total Plate Count (TPC), which were analyzed descriptively. The results showed that collagen yield is 5,021%, protein content is 76,89%, water content is 4,05%, fat content is 0,57%, and ash content is 0,20%. The results of the Kruskal Wallis test show that natural liquid soap with the addition of collagen has a significant effect on aroma, viscosity, and appearance but has no effect on the impression during its use, the imression after use, and the amount of foam. The ANOVA test shows that collagen has a significant effect on the viscosity of natural liquid soap. The characteristics of the selected natural liquid soap pH 7,41, foam stability 83,33%, free fatty acids 2,5%, and ALT 3,4×103, all of which meet the requirements of SNI (1996).